2012
DOI: 10.1111/j.1440-1746.2012.07292.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of autoimmune hepatitis and comparison of two diagnostic criteria in Korea: A nationwide, multicenter study

Abstract: Autoimmune hepatitis in Korea is mostly type I, showing a mean age of 53 years with comparable clinical features to other countries. The concordant rate of the two diagnostic criteria was rather low with modest sensitivity of the simplified criteria. Further studies on the validation of the diagnostic criteria are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
4
39
0
6
Order By: Relevance
“…Overall, the profiles of our patients were consistent to what have been shown in the literature, West and East [1,[3][4][5]. There was a female predominance, advanced disease stage at presentations, presence of other autoimmune disease, response to treatment, and mortality rates.…”
supporting
confidence: 88%
“…Overall, the profiles of our patients were consistent to what have been shown in the literature, West and East [1,[3][4][5]. There was a female predominance, advanced disease stage at presentations, presence of other autoimmune disease, response to treatment, and mortality rates.…”
supporting
confidence: 88%
“…Similar figures were reported from several studies. Kim and his colleagues reported that 22.7% of their patients had liver cirrhosis at presentation in a cohort of Korean AIH patients [20] . Cirrhosis was more prevalent in AIH patients who presented with jaundice, reaching 50% in one European study [21] and 43% in our series.…”
Section: Discussionmentioning
confidence: 99%
“…A previous nationwide Korean study reported autoimmune thyroiditis as the most common concurrent autoimmune disease, followed by systemic lupus erythematosus. [24] In this study, we could not confirm the diagnosis of autoimmune thyroiditis; however, thyroid hormone was prescribed in 3.6% of patients with AIH. Therefore, it is conceivable Epidemiology of AIH in South Korea that autoimmune thyroiditis was present in 3.6% or less.…”
Section: Discussionmentioning
confidence: 65%
“…Previous study also reported that 25% of newly diagnosed patients were not treated. [24] The strength of the present study is its population-based design. The NHI claims data covers > 95% of the entire Korean population.…”
Section: Discussionmentioning
confidence: 99%